First report of ranavirus mortality in a common snapping turtle Chelydra serpentina. - McKenzie CM; Piczak ML; Snyman HN; Joseph T; Theijin C; Chow-Fraser P; Jardine CM (Inter-Research Science Center, 2019)
An adult male snapping turtle with marked palpebral edema and multifocal skin ulceration was found alive in a marsh in southern Ontario in summer 2017. The turtle was transported to a rehabilitation facility and died 4 d after arrival. The carcass was submitted to the Canadian Wildlife Health Cooperative for post-mortem examination. Gross lesions included ulcerative conjunctivitis, necrotizing stomatitis, and splenomegaly. Microscopically, this corresponded to multisystemic fibrinonecrotizing vasculitis and severe fibrinous splenic necrosis. Liver tissue tested positive for frog virus 3-like ranavirus and negative for herpesvirus via polymerase chain reaction. The gross and microscopic lesions were consistent with previous reports of ranavirus infection in turtles and were severe enough to have been the cause of death in this case. This is the first report of morbidity and mortality in a common snapping turtle with a ranavirus infection, and the first reported case of ranavirus infection in a reptile in Canada. Ranaviruses are considered to be an emerging infectious disease in chelonians as they are increasing in distribution, prevalence, and host range.
Keywords: 3009 Veterinary Sciences; 30 Agricultural, Veterinary and Food Sciences; Emerging Infectious Diseases; Infectious Diseases; Infection; 3 Good Health and Well Being; Animals; Animals, Wild; Canada; Male; Ranavirus; Reptiles